ANALISIS IMPLEMENTASI KEBIJAKAN PERATURAN PEMERINTAH NOMOR 39 TAHUN 2018 TENTANG KEPROTOKOLAN PADA BAGIAN PROTOKOL DAN KOMUNIKASI PIMPINAN SEKRETARIAT DAERAH PEMERINTAH KABUPATEN LAMPUNG BARAT - Adrian Tawai; Rola Pola Anto; Kusuma Wardani Dwi Putri (Universitas Bandar Lampung (UBL), 2021)
The prevailing regulations in regulating the implementation of technical seraca protocol are stipulated in Government Regulation No. 39 of 2018 concerning the Implementation of Law No. 9 of 2010 on Protocol. In the regulation regulates various technical implementation of protocol ranging from the layout of the venue, ceremony, respect, regulation of the protocol of state guests, government guests and guests of foreign state institutions, as well as the arrangement of visits and banquets. On the other hand, members of the protocol of the West Lampung Regency District Government still do not understand many rules governing the protocol itself, this often happens to the placement of the order of invited guests who have not complied with the applicable rules. This study aims to identify and analyze the Government Regulation Policy No. 39 of 2018 on Protocol and Communication in the Protocol and Communication Section of the Regional Secretariat of the Government of West Lampung Regency. The research method used in this study is qualitative data analysis. Where researchers jump directly into the field to obtain data from the beginning to the end of the study. The sources and types of data used are primary and secondary data. Data collection method by means of literature research, observation, interview, and documentation.Based on the data analysis that has been done, the implementation of Government Regulation No. 39 of 2018 on Protocol and Communication in the Protocol and Communication Section of the Regional Secretariat of West Lampung Regency has not gone well because there are still many protocol members who do not understand the rules governing protocol, Factors Inhibiting the Implementation of PP No. 39 of 2018 on the first protocol is still the lack of human resources with ASN status, Second, there are still many members of the protocol who have not followed the training of protocol either held by the Ministry Institutions or provincial government, Third, still lack of existing facilities and infrastructure.